Phelipanche sevanensis (Orobanchaceae): a new species from the Caucasus, and nomenclatural notes on similar species - Piwowarczyk, Renata; Pedraja, Óscar Sánchez; Moral, Gonzalo Moreno (Phytotaxa, 2017)
Phelipanche sevanensis (Orobanchaceae) is described as a new species from the Lesser Caucasus in Armenia. It grows on steep rocky slopes around Lake Sevan in semi-arid mountain steppe communities, where it parasitises Heracleum trachyloma, a Caucasian endemic. A detailed description, illustrations, and a comparison with the most similar species, especially P. heldreichii, are provided. We also present nomenclatural notes about P. coelestis, P. hohenackeri, P. persica and P. simplex. Three lectotypes are designated, and two new combinations are proposed.